Flow characteristics of 3-D turning diffuser using particle image velocimetry - Nordin, Normayati; Abdul Karim, Zainal Ambri; Othman, Safiah; Raghavan, Vijay R.; Batcha, Mohd Faizal Mohideen; Hariri, Azian; Basharie, Siti Mariam (American Institute of Physics, 2017)
It is often necessary in fluid flow systems to simultaneously decelerate and turn the flow. This can be achieved by employing turning diffusers in the fluid flow systems. The flow through a turning diffuser is complex, apparently due to the expansion and inflexion introduced along the direction of flow. The flow characteristics of 3-D turning diffuser by means of varying inflow Reynolds number are presently investigated. The flow characteristics within the outlet cross-section and longitudinal section were examined respectively by the 3-D stereoscopic PIV and 2-D PIV. The flow uniformity is affected with the increase of inflow Reynolds number due to the dispersion of the core flow throughout the outlet cross-section. It becomes even worse with the presence of secondary flow, 22% to 27% of the mean outlet velocity. The flow separation takes place within the inner wall region at the point very close to the outlet edge and the secondary flow vortex occurs dominantly within half part of the outlet cross-section.